Anatomy of adult Megaphragma (Hymenoptera: Trichogrammatidae), one of the smallest insects, and new insight into insect miniaturization - Polilov, Alexey A. (PloS one, 2017)
The body size, especially in cases of extreme reduction, is an important characteristic that strongly determines the morphology, physiology, and biology of animals. Miniaturization is a widespread trend in animal evolution and one of the principal directions of evolution in insects. Miniaturization-related features of insect morphology have been subject to intensive studies during the last few years, but the structure of the smallest insects remains insufficiently known. It is especially important to study hymenopterans of the genus Megaphragma, which include the smallest flying insects and a species in which an almost anucleate nervous system was recently discovered. This article is the first detailed study of the external and internal morphology of adults of Megaphragma mymaripenne and M. amalphitanum using histological methods, 3D computer modeling and other techniques. It is shown that in spite of the extremely small size the organization of Megaphragma retains a considerkable level of structural complexity. On the other hand, miniaturization leads to re-organizations of several organ systems. Unique structural features related to miniaturization have been found in both species: lysis of cell bodies and nuclei of neurons at late stages of pupal development, absence of the heart, and considerable reductions in the set of muscles. Comparative analysis of structure in the smallest insects representing different taxa has revealed common features of the evolutionary process of miniaturization in insects.